Increasing threshold voltage and reducing leakage of AlGaN/GaN HEMTs using dual-layer SiNx stressors. (5th March 2020) - Cheng, Wei-Chih; He, Minghao; Lei, Siqi; Wang, Liang; Wu, Jingyi; Zeng, Fanming; Hu, Qiaoyu; Wang, Qing; Zhao, Feng; Chan, Mansun; Xia, Guangrui (Maggie); Yu, Hongyu
Abstract: In this work, AlGaN/GaN HEMTs with dual-layer SiN x stressors (composed of a low-stress layer and a high-stress layer) were investigated. The low-stress padding layer solved the surface damage problem which was caused during the deposition of the high-stress SiN x and provided a good passivated interface. The HEMTs with the dual-layer stressors showed a 1 V increase in the threshold voltage ( V th ) with comparable DC and RF amplification performance to the baseline devices. Moreover, the off-current ( I off ) was shown to be reduced by one to three orders of magnitude in the strained devices. The reduction in the off-currents was a result of the lower electric field in AlGaN, which suppressed the gate injection current. These improvements using the dual-layer stressor scheme supports strain engineering as an effective approach in the pursuit of the normally-off operation of AlGaN/GaN HEMTs.